Regulation of the temperature of an individual heat point by changing the speed of the asynchronous motor - T. V. Sinyukova; A. V. Sinyukov (Известия высших учебных заведений: Проблемы энергетики)
THE PURPOSE. To develop and investigate a mathematical model of an operating object – an individual heat point with two methods of controlling the temperature of the coolant. In the first case, the control of the temperature of the coolant is considered, with the help of a control valve installed on a real object. In the second case, a more reliable and less energy-consuming solution is proposed – replacing the control valve with a frequency- controlled electric drive operating according to the proposed optimal algorithm. METHODS. When solving this problem, the method of computer simulation modeling, implemented by means of Matlab Simulink, was used.RESULTS. The article deals with the problems that arise during the operation of an individual heating point. Possible solutions to the problem associated with the failure of the control valve are given. A solution for regulating the temperature of the coolant is proposed, based on the use of a frequency-controlled electric drive of the electric pump. To implement the proposed solution, no redevelopment of the premises is required, only the installation of a frequency converter on the pump already available in the device of an individual heat station is necessary. CONCLUSION. The conducted research has a practical focus, since the proposed solution is implemented at the existing facility. The use of a frequency-controlled electric drive of a centrifugal pump made it possible to increase the reliability of the existing facility. The results obtained during the simulation allow us to draw a conclusion about the feasibility of using the proposed solution.